PENGARUH GREEN MARKETING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA ORGANIK CHICKEN CABANG PT.ELHA NARITA PERKASA PEKANBARU - Jessica Aura Yasmeri; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is based on an existing phenomenon where products that pay attention to their impact on the environment or green marketing can be one of the factors that influence consumer purchasing decisions, because it relates to the company's efforts to pay attention to products from the process to the hands of consumers from competitors who use the green concept. marketing too, so that it can be used by consumers as a basis for deciding between buying or not a product being offered. The problem in this study is whether there is a significant influence between green marketing and brand image with the purchasing decision of O'Chicken Pekanbaru chicken culinary. This research was conducted at O'Chicken Pekanbaru which is located at Jalan Tengku Bey Number 20, Air Dingin Village, Kec, Bukit Raya, Pekanbaru City, Riau.      The sample in this study amounted to 100 respondents who were taken based on the Slovin formula with the sampling technique using the accidental sampling method. Data collection techniques through observation, interviews, questionnaires and documentation. Furthermore, the authors analyze the data using quantitative methods using research instrument tests, classical assumption tests and hypothesis testing. From the results of this study, obtained a simple linear regression equation as follows: Y = 10.340 + 0.581X means that the green marketing variable has a positive effect on the purchasing decision variable. And the simple linear regression equation Y= 11.510 + 0.847X means that the brand image variable has a positive effect on the purchasing decision variable. This is also tested. With a t test of t count = 4.380 > t table 1.660 and significance = 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected, namely the green marketing variable has a significant effect on purchasing decisions, and with a t test of t count = 4.078 > t table 1.66055 and significance = 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected, which means partially brand image has a significant influence on purchasing decisions on organic chicken PT. Elha Narita Perkasa Pekanbaru. For the Coefficient of Determination Test (R2) the green marketing variable obtained a value (R square) of 0.174 or 17.4%. This shows that the percentage contribution of green marketing and brand image variables to purchasing decisions is 17.4%, while the remaining 82.6% is influenced by other variables not included in this study. and for the brand image variable, the number (R Square) is 0.145 or 14.5%. This shows that the percentage contribution of green marketing and brand image variables to purchasing decisions is 17.4%, while the remaining 82.6% is influenced by other variables not included in this study. and for the brand image variable, the number (R Square) is 0.145 or 14.5%. This shows that the percentage contribution of the influence of the brand image variable on purchasing decisions is 14.5%, while the remaining percentage of 85.5% is influenced by other variables that are not included in other variables that are not included in this research variable. In the correlation coefficient, it is known that the R value is 0.17. This means that the correlation between the independent variable and the dependent variable has a strong relationship. Keywords: Green Marketing,Brand Image, Buying Decision